Analysis of Cooperation and Motivation Nurse in Implentation Nursing of Family - Siti Nur Kholifah; Nursalam Nursalam; Meriyana Meriyana; Ahsan Ahsan; Minarti Minarti; Dwi Ananto Wibrata; Noer Saudah (Intelektual Pustaka Media Utama, 2016)
Cooperation of nurses needed in helping to resolve the client's problem. Cooperation was an important element in developing quality of human resources and improving performance. The general objective of this study was to identify cooperation-relation nurse with motivation in implementing the family nursing care at Surabaya city. The research method was analytical observational with cross sectional approach. The population of this study was 175 nurses at local government clinic at Surabaya city. The sample size of this study was 122 gained by probability sampling. The research variables include the cooperation of nurses and motivation in implementing family nursing care. Instrument used questionnaire. Bivariate analysis of the data was done by Spearman correlation test. Limit the test of significance is 0.05. The test resulted that there was a relationship of cooperation with the motivation of nurses in implementing family nursing care (p = 0.03). Nurses should develop cooperative relationships in order to increase their motivation to carry out the nursing care of the family.